(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Soccer is a sport practiced worldwide, being a fundamental part of its practice at an early age, one of its main foundations is the shot at goal, which is the technical action that involves the throwing of the ball into the goal of the opposing team, which can run with the lower extremities, trunk and head. This action is directly related to coordinative capacities; which are an important element in formative soccer training, being fundamental in this research, to establish as an objective, the base of the importance of training special coordination skills in shooting at goal in U-12 soccer players. The methodology was based on a theoretical review study, which uses methods such as analytical - synthetic for the processing and analysis of information, as well as inductivedeductive to go from the specific, such as the shot at the door, to the general As is the coordinative development of the athlete in the execution of the technique of shooting at the door, the type of investigation is documentary, through which an analysis of the information obtained from secondary data is established. Among the fundamental findings it was possible to determine that the different authors determine in their studies that coordination exercises enhance the technique of children at an early age, therefore, they improve aspects such as control, stability and shooting at goal.